Analysis Of Road Damage Repair Using SDI (Surface Distress Index) Method : Case Study: KS. Tubun St. – Merpati St., Tegal City - Ridwan, Muhammad Alif Ridwan; Izzuddin, M. Daffa; Nailulloh, Raditya Faris; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Road damage is something that must be addressed immediately because roads play an important role such as connecting remote areas to economic centers, connecting public services, providing mobility for humans or goods, and other social activities that cross the KS Tubun - Merpati road, Tegal City. Using a quantitative approach, data were collected via surveys on the street, focusing on the road that have some crack or broken to collect the data that been using to analyze the category of road damage. This study aims to identify the types of damage on KS Tubun Road and Merpati Road along STA 0+000 to STA 0+1200 and calculate the total SDI value to determine the value of road pavement conditions using the Surface Distress Index (SDI) method. The results obtained for the analysis of the types of damage that occurred on Jalan KS Tubun and Jalan Merpati at STA 0+000 to STA 0+1200, based on the SDI method, there are elements of damage, namely edge damage of 9.87 m2, vertical cracks of 7 m2, longitudinal cracks of 3 m2, holes with a total area of ​​​​8411.7m2, patches of 4020.54 m2, sloping areas of 48m2, road depressions of 323m2, road fatness of 20m2, road aggregate wear of 210m2, and railroad crossings of 1960m2. The results of the SDI calculation show that the road conditions on the KS Tubun and Jalan Merpati sections are in good condition.